Habilidades investigativas en estudiantes de grado en carreras pedagógicas. Un saber necesario en la sociedad globalizada. - Mena Gallardo, Alisson Anahí (2024)
Investigative skills are an essential component of the training of competent professionals in any area, and particularly in education. In a globalized society, educators must have the ability to generate knowledge adaptable to changes, to contribute to the improvement of educational quality. Through these skills, they will be able to develop and implement novel pedagogical tactics, adapt to changes in educational contexts and contribute to the long-term development of society. However, there is a knowledge gap about the specific research skills that students should acquire and improve. Through this study, we sought to fill this knowledge gap by identifying the key research skills necessary for the development of education. The objectives set out in this research sought to understand the level of development of investigative skills in students of pedagogical careers, identify the factors that influence their acquisition and evaluate the impact of these skills on their future professional practice. In addition, look for the strengths and weaknesses, to propose some strategies and thus optimize and strengthen the investigative skills of information search in students of pedagogical careers. Through the methodological process practiced, the opinion of the students of pedagogical careers of the National University of Loja is collected, through the application of a questionnaire based on a Likert scale with five categories, which cover options from “never” to “always”. This approach allows measuring the frequency with which participants apply research skills in the educational context, which allows obtaining significant data on the digital competence of participants in their daily activities. Regarding the results, through the proposed field research, a comprehensive vision was provided about the state of research skills in students of pedagogical careers, in which it is concluded that there is an imperative need to seek to strengthen the training strategies that encourage the development of investigative skills. These findings highlighted the need to enrich pedagogical training with a more proactive approach towards investigative skills, using research practices from early stages, as well as constant updating through academic programs that apply and have designed effective didactic proposals that use appropriate tools for the context of globalized society. Keywords: Investigative skills; Education; Pedagogy; Globalization; education development; Pedagogical tactics.